European integration and the clash of civilizations - Žygimantas Pavilionis (Politologija)
Recently, on March 12, 1998, the British Foreign Secretary Robin Cook announced the day to be "a historic date, save contemporary and the future member-states of the European Union, Europe, once and for long decades divided, have come together into unity". By saying this, the Foreign Secretary touched upon a pressing issue of today, namely, the question - what is Europe on this day?